Study on Sensitivity of Microphysics for the Simulation of Rainfall for the Month of May 2015 over Bangladesh using High Resolution WRF-ARW Model - Khan, Md Salman; Alam, MM (Journal of Engineering Science, 2020)
In this research the Advanced Research WRF (ARW) model v3.8.1 has been used to simulate the rainfall of May 2015 all over Bangladesh. The model was configured in nested domain with 18 and 6 km horizontal grid spacing with 100 × 96 and 103 × 127 grids in the east-west and north-south directions, respectively with 30 vertical levels. The Lin et al., WSM6, Thomson, Morrison Double-Moment (M-2Mom), Stony Brook University (SBU), and WDM6 microphysics schemes coupling with Kain-Fritsch (KF) cumulus parameterization (CP) scheme have been used to simulate the monthly total rainfall, heavy rainfall, monthly rainy days and heavy rainy days for the month of May 2015 at all meteorological stations of Bangladesh. The simulated results are compared with the observed results of 33 meteorological stations of Bangladesh Meteorological Department (BMD) and Precipitation Estimation from Remotely Sensed Information using Artificial Neural Networks (PERSIANN) output. Relative standard deviation of all observed, PERSIANN and model simulated parameters have been analyzed and compared. The maximum monthly observed rain in May 2015 at Sylhet was 752 mm but WSM6, M-2Mom and WDM6 schemes have simulated 831, 788 and 742 mm for day 1 prediction; WSM6, WDM6 and SBU-Lin schemes have simulated 757, 916 and 981 mm for day 2 prediction and WSM6 and WDM6 schemes have simulated 741 and 925 mm for day 3 prediction, respectively and all other MPs have simulated much higher rainfall at domain (D1). The WDM6, M-2Mom and Lin et al. schemes have simulated 744, 807 and 923 mm for day 1 prediction, WSM6 and WDM6 schemes have simulated 714 and 877 mm for day 2 predictions and WSM6, SBU-Lin and Lin et al. schemes have simulated 802 and 913 and 998 mm, respectively for day 3 predictions at domain (D2). The relative standard deviation (RSD) has minimum at D1 and D2 for WDM6 scheme for day 1 prediction and WSM6 scheme for day 2 and day 3 predictions for the monthly total rainfall and heavy rainfall of May 2015. The results suggest that as the forecast time increased the amount of total rain and also heavy rain is increased. As a result RSD is also increased for all MPs. WDM6 scheme gives the better performance of rainfall and rainy days all over the country. Journal of Engineering Science 11(1), 2020, 43-60